Perceived posttraumatic growth in cardiac patients: A systematic scoping review. Issue 3 (5th February 2022) - Lee, Sharon Y.; Park, Crystal L.; Laflash, Samantha
Abstract: Despite the life‐threatening nature of many cardiac conditions, patients often report perceived posttraumatic growth (PPTG) in their recovery. To date, this research remains scattered across the literature, and no systematic review across cardiac patient populations is available. To understand the state of the literature on PPTG in cardiac patients, we conducted a systematic scoping review, aiming to (a) describe patient populations included, (b) characterize associations between PPTG and mental and physical health indices, (c) identify potential psychosocial resources that moderate or mediate the effects of a cardiac condition on PPTG, and (d) describe and critique study methodologies. A systematic search was conducted on June 21, 2021, using the PubMed and PsycInfo databases. Two authors independently screened the results for eligibility and resolved discrepancies before extracting study data. We identified 21 studies that met the search and eligibility criteria (i.e., original, peer‐reviewed, English language). Most studies focused on a single cardiac condition (61.9%), with myocardial infarction the most common. PPTG was studied in relation to myriad mental health and physical health indices. The findings suggested that appraisal and coping may mediate and psychosocial resources (e.g., social support) may moderate the effects of a cardiac condition on PPTG. The generalizability of results is limited, as most studies employed a cross‐sectional design with mostly male and majority White samples. Future research would benefit from studying PPTG in more diverse cardiac populations, assessing appraisals of the cardiac condition as traumatic, measuring posttraumatic depreciation in tandem with PPTG, and conducting prospective studies.